Employee Retention Model with Variables of a Supportive Work Environment Mediated By Organizational Involvement (Study at PT. Carana Bunga Persada) - Rahmani, Shinta; Prayoga, Candry (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study aimed to examine the effect of a supportive work environment and organizational Involvement on employee retention, as well as the mediation effect of organizational Involvement on the relationship between supportive work environment and employee retention at PT. Carana Bunga Persada. The study was conducted on 119 people consisting of 78 men and 41 women who were working at PT. Carana Bunga Persada. The data was then processed using the path analysis technique using the SPSS version 23 program. The results showed that a supportive work environment positively affects employee retention. Organizational Involvement also has a positive effect on employee retention. Organizational Involvement significantly mediated the relationship between a supportive work environment and employee retention. Based on the results of the study, the researchers made implications and suggestions for further research